Prevalence of Multidrug-Resistant and Biofilm-Forming Salmonella enterica in Beef from Peshawar - Muhammad Jawad Ullah; Kafeel Ahmad; Faryal Khattak; Fawad Inayat; Sawaira Huriya; Naila Menhaj (Faculty of Medicine, Universitas Padjadjaran, 2026)
Salmonella enterica is a major public health concern and is frequently linked tobeef contamination, particularly in developing countries where the emergence of multidrug-resistant (MDR) strains has increased health risks associated with the consumption of contaminated meat. This study aimed to determine the prevalence, seasonal distribution, antimicrobial resistance patterns, and biofilm-forming ability of S. enterica isolated from different points of the beef supply chain in Peshawar, Pakistan. A total of 250 beef samples were collected from retail shops, butcheries, and slaughterhouses across 23 locations between February 2021 and February 2023. The isolates were identified using standard biochemical tests, and antimicrobial susceptibility was evaluated against 16 antibiotics using the Kirby–Bauer disk diffusion method. Biofilm-forming ability was assessed using a quantitative microtiter plate assay. The overall prevalence of S. enterica was 68.0% (170/250), and 150 isolates were further subjected to molecular analysis. A clear seasonal pattern was observed, with the highest prevalence in summer (85.7% in August) and the lowest in winter (43.8% in January), showing a strong positive correlation with temperature (r=0.89, p<0.001). Spatial analysis showed higher odds of contamination near slaughterhouses (OR=2.21, 95% CI: 1.15–4.23) and in urban centers (OR = 2.41, 95% CI: 1.38–4.22) compared to rural areas. High resistance levels were detected against azithromycin (87.3%), tetracycline (61.3%), and streptomycin (48.0%). The MDR phenotype was observed in 56.7% of isolates with a mean MAR index of 0.342. Biofilm formation was detected in 87.3% isolates, and strong producers exhibited a higher prevalence of MDR